Results of Modeling Sources of Magnetic Anomalies in the Earth’s Crust in the Middle Urals - Martyshko, P. S.; Fedorova, N. V.; Rublev, A. L. (Doklady earth sciences, 2022)
The results of studying the structural features of an anomalous magnetic field and modeling sources in the Earth’s crust of the Middle Ural region are presented. A territory of 880 × 500 km 2 covers the eastern part of the East European Platform, the Middle Urals, and the western part of the West Siberian Plate. Within this area, intense linear anomalies are observed in the anomalous magnetic field in the Urals and Western Siberia, and large regional anomalies are identified within the East European Platform. The interpretation of airborne magnetic data was conducted using original parallel algorithms for separating magnetic field sources by depth and solving the structural inverse problem of magnetometry. As a result, a model of magnetic field sources in the layers of the Earth’s crust of the region under study was constructed for various values of magnetization.